Pelatihan E-Commerce dan Inovasi Pengemasan Bakul Lontar bagi Kelompok Tani Gula Aren Desa Umpungeng Kabupaten Soppeng - Rusdi Rusdi; Muh Said; Hasnawi Haris; Dalilul Falihin; Sagita Ramadhana (Humanis, 2026)
This community service program aimed to improve the capacity of the Palm Sugar Farmers Group in Umpungeng Village, Soppeng Regency, in product packaging and digital marketing. The main problems faced by the partner were limited market access, dependence on local traders, lack of packaging innovation, and limited skills in managing online stores. The program was implemented through partner coordination, needs identification, training on lontar basket packaging, digital marketing training, online store development practice, and mentoring in managing products on e-commerce platforms. The activity involved members of the farmers group, particularly lontar basket artisans and palm sugar producers. The results showed an improvement in the participants’ skills in producing more attractive, environmentally friendly, and locally based lontar basket packaging. In addition, participants were able to create online store accounts, upload product photos, write product descriptions, and understand digital promotion strategies through e-commerce platforms. The program also encouraged broader market access for palm sugar products, although challenges remained in terms of internet access and participants’ adaptation to new technology. Therefore, this program contributed to strengthening entrepreneurial capacity, improving local product competitiveness, and increasing the marketing independence of the farmers group.